The revaluation of crafts and its impact on cultural identity. The case of La Pila, Ecuador - Santos Moreira, Vanessa Teresa (2024)
Various socioeconomic and cultural factors shape the cultural identity of a locality. One key factor influencing cultural identity is the revaluation of craft production. This article examined the relationship between the revaluation of crafts and cultural identity by analysing the performance of the key actors involved in craft production. The study used a quantitative methodology with a descriptive, correlational, and transactional approach. The data was collected through surveys and the Likert scale from 188 individuals. The study discovered a positive and statistically significant relationship between the appreciation of crafts and their influence on cultural identity.